EFEK HOAX COVID-19 BAGI IGENERATION DI KABUPATEN BURU - A. Yusdianti Tenriawali; Suryani Suryani; Ibnu Hajar; M Chairul Basrun Umanailo (Potret Pemikiran, 2020)
ABSTRACTIndonesia is prone to being affected by hoaxes because the number of internet accesses reaches more than 50 percent of Indonesia's population. The impact of the distribution of hoax content is relatively diverse. Starting from causing anxiety and fear in some community groups to becoming national attention through mass media coverage. This study aims to determine how the Covid-19 hoax effect for iGeneration in Buru Regency. This research is a field research. The population in this study were students of Universitas Iqra Buru, Buru Regency, Maluku. Data collection techniques in this study using observation, interviews, and documentation. The data that has been collected is analyzed based on the effect theory and mass communication function to determine the effects of hoax news. The results showed that the hoax issues that most circulated on social media during the Covid-19 pandemic were SARA hoaxes, health hoaxes, and politics hoaxes. Based on the research results, it can be seen that there is a tendency for SARA hoaxes and political hoaxes to have an affective effect on the community, especially for iGeneration in Buru Regency. Health hoaxes tend to have a conative effect on the community. Keywords: Social media; Hoaks Covid-19; iGenerationABSTRAKIndonesia rentan terpengaruh hoaks karena jumlah pengakses internet mencapai lebih dari 50 persen dari jumlah penduduk Indonesia. Dampak yang ditimbulkan dari sebaran konten hoaks itu relatif beragam. Mulai dari menimbulkan keresahan dan ketakutan di sebagian kelompok masyarakat hingga menjadi perhatian nasional melalui pemberitaan media massa. Penelitian ini bertujuan untuk mengetahui bagaimanakah efek hoaks covid-19 bagi iGeneration di Kabupaten Buru. Penelitian ini merupakan penelitian lapangan. Populasi dalam penelitian ini adalah mahasiswa Universitas Iqra Buru, Kabupaten Buru, Maluku. Teknik pengumpulan data dalam penelitian ini menggunakan observasi, wawancara, dan dokumentasi. Data yang telah terkumpul kemudian dianalisis berdasarkan teori efek dan fungsi komunikasi massa untuk mengetahui efek berita hoaks. Hasil penelitian menunjukkan isu hoaks yang paling banyak beredar di media sosial selama pandemi Covid-19 adalah hoaks SARA, kesehatan, dan politik. Berdasarkan hasil penelitian terlihat adanya kecenderungan hoaks SARA dan hoaks politik memberi efek afektif kepada masyarakat, khususnya bagi iGeneration di Kabupaten Buru. Adapun hoaks kesehatan cenderung memberi efek konatif kepada masyarakatKata kunci: Media sosial; Hoaks Covid-19; iGeneration